Learning Difficulties of High School Students in Understanding the Material of Human Reproductive Systems Triggering Misconceptions - Naning Wahyuni; Hadi Suwono; Umie Lestari (Jurnal Pendidikan Sains, 2019)
Abstract: Human Reproductive System is a basic concept in biological sciences that is related to daily life and interesting for high school students. Complicated learning materials make it difficult for students to construct their knowledge and understand the concepts. Survey research using a questionnaire was conducted to determine the causes of difficulties for high school students in understanding the Human Reproductive System concepts. Respondents were grade XII science students and two teachers. The data obtained were analyzed descriptively. The research findings indicate that students’ difficulties are due to (1) the extensive usage of scientific terms, (2) abstract concepts, (3) monotone, and (4) inadequate sources of information. The implication of this result is that teachers are required to elaborate appropriate strategies and textbooks to lead students getting accurate knowledge. Key Words: learning difficulties, senior high school students, human reproductive system, teacher, textbook, misconception